2018
DOI: 10.3329/jujbs.v7i1.37973
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fresh rice straw and water levels on CO2-C gas emission, soil organic carbon content and rice production

Abstract: An experiment was conducted at Bangladesh Institute of Nuclear Agriculture (BINA) farm, Mymensingh, Bangladesh during 2010-2011 to find out the effect of different water and organic residue levels on rice production and soil organic carbon content. Organic carbon rates from rice straw (0.5, 1.0, 1.5 and 2.0 t C ha -1 including control) were evaluated under alternate wetting and drying (AWD) and continuous flooding (CF) systems. Each treatment also received the recommended dose of chemical fertilizers excluding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
(10 reference statements)
1
3
0
Order By: Relevance
“…Similar to the observed different CO 2 fluxes in soil respiration during the daytime in response to the different water management practices, Hossain [58] also observed that alternate wetting and drying (AWD) increased CO 2 emission by 16% compared to continuous flooding (CF). This is congruent with our data (Table 1) on night soil respiration under AWD treatment when average total CO 2 flux was higher compared to flux under CF treatment.…”
supporting
confidence: 63%
“…Similar to the observed different CO 2 fluxes in soil respiration during the daytime in response to the different water management practices, Hossain [58] also observed that alternate wetting and drying (AWD) increased CO 2 emission by 16% compared to continuous flooding (CF). This is congruent with our data (Table 1) on night soil respiration under AWD treatment when average total CO 2 flux was higher compared to flux under CF treatment.…”
supporting
confidence: 63%
“…The increased soil organic carbon is due to the addition of organic manures which improved the Physico-chemical properties of the soil, especially in sandy clay loam soil. The addition of organic manures along with inorganic fertilizer in a continuously flooded condition paves the way for the highest organic carbon accumulation which is a main factor for the improvement of soil quality index and minimized environmental hazards [14]. Furthermore, positive interaction between the organics with inorganic NPK eventually increased the overall growth components both above and below ground which attribute the entire physiological function by way of providing nutrients and its relative growth hormones which in turn leads accumulation of more photosynthates.…”
Section: Resultsmentioning
confidence: 99%
“…Combined use of chemical fertilizers, 2.0 t C ha-1 fresh rice straw and continuous flooding system performed better results to reduce CO2-C gas emission, increased organic carbon and rice production with maintaining optimum soil pH level with sustainable rice production (Hossain, 2018).…”
Section: Inm On Co 2 Emission In Rice Productionmentioning
confidence: 99%
“…Akhilesh and Nandan (2016) noticed that a higher soil organic carbon stock (43.77 t ha (Naresh et al, 2017). A higher soil organic carbon with a value of 7.8 and 8.6 g kg -1 were recorded with the application of FYM @ 12.5 t ha -1 integrated with 100% RDF + Azospirillum and Phosphobacteria @ 2 kg ha -1 over other organic manure combinations in the successive years of rice crop (Ravikumar and Ganapathy, 2018).The application of organic manures along with chemical fertilizer and continuous flooded condition paves the way for the highest organic carbon accumulation which is a key factor for improvement of soil quality and minimized environmental pollution (Hossain, 2018).…”
Section: Inm On Carbon Dynamics In Rice Productionmentioning
confidence: 99%